Symmetric molecules with 1, 4-triazole moieties as potent inhibitors of tumour-associated lactate dehydrogenase-A. (1st January 2018) - Altamimi, Abdul-Malek S.; Alafeefy, Ahmed M.; Balode, Agnese; Vozny, Igor; Pustenko, Aleksandrs; El Shikh, Mohey Eldin; Alasmary, Fatmah A. S.; Abdel-Gawad, Sherif A.; Žalubovskis, Raivis
Abstract: A series of symmetric molecules incorporating aryl or pyridyl moieties as central core and 1, 4-substituted triazoles as a side bridge was synthesised. The new compounds were investigated as lactate dehydro-genase (LDH, EC 1.1.1.27) inhibitors. The cancer associated LDHA isoform was inhibited with IC50  = 117–174 µM. Seven compounds exhibited better LDHA inhibition (IC50 117–136 µM) compared to known LDH inhibitor – galloflavin (IC50 157 µM).